The Effectiveness of the Use of Newspaper and Magazine in Improving Students’ Writing Skills - Tinambunan, Tedty; Sinaga, Maria Novayanti (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2018)
This study aimed to investigate (1) whether the use of newspaper is more effective than that of magazine in improving students’ writing skills, (2) whether the use of newspaper is more effective than that of conventional medium in improving students’ writing skills, (3) whether the use of magazine is more effective than that of conventional medium in improving students’ writing skills, and (4) the most effective medium of all: newspaper, magazine, and conventional medium in improving students’ writing skills. This study was a quasi-experimental research using Pretest-Post-test Control Group Design. The data were collected in SMA Negeri 6 Yogyakarta. The sample of the research was the students of class X7, X8, and X9 which were determined by using cluster simple random sampling. There were four hypotheses of this study and the research findings revealed that the hypotheses were accepted. It was indicated by all of the Sig values, which were lower than the level of significance (0.05). Further, the implications on classroom instruction and policy making are discussed